Modification of Oxygen-Ionic Transport Barrier of BaCo0.4Zr0.1Fe0.4Y0.1O3 Steam (Air) Electrode by Impregnating Samarium-Doped Ceria Nanoparticles for Proton-Conducting Reversible Solid Oxide Cells. Issue 12 (15th July 2019) - Saqib, Muhammad; Lee, John-In; Shin, Ji-Seop; Park, Kwangho; Kim, You-Dong; Kim, Ki Buem; Kim, Jung Hyun; Lim, Hyung-Tae; Park, Jun-Young
Abstract : A reliable and high performance proton-conducting reversible solid oxide cell (P-RSOCs) is developed to generate electricity in a protonic ceramic fuel cell (PCFC) mode and to generate hydrogen gas in a protonic ceramic electrolysis (PCEC) mode in a single electrochemical device. Herein we propose a modified triple conducting (H + /O 2− /e − ) steam (air) electrode through the infiltration of an Sm0.2 Ce0.8 O2-δ (SDC) oxygen-ionic conductor, because the polarization resistance ( Rp ) of P-RSOCs mainly comes from the steam (air) electrode in both the operational modes. The SDC-infiltrated nanoparticles on the composite BaCo0.4 Zr0.1 Fe0.4 Y0.1 O3+δ (BCZFY)-BaCe0.7 Zr0.1 Y0.2-x Ybx O3-δ (BCZYYb) electrode result in a considerable improvement in the oxygen reduction reaction and oxygen evolution reaction catalytic activity at 600–700°C due to the extension of electrochemical active sites with the increasing of surface area. In addition, the enhanced ionic conduction of a triple conducting composite using infiltrated oxygen-ionic SDC conductors leads to an effective decrease in the Rp (1.388→1.079 Ω·cm 2 at 600°C symmetric cell) with improved cell performance in both the PCFC and PCEC modes. Furthermore, the NiO-BCZYYb anode-supported cell with the SDC-infiltrated composite BCZFY-BCZYYb air electrode shows excellent durability in the PCFC and PCEC modes without any degradation during 250 h each at 650°C.